2020
DOI: 10.18239/ensayos.v35i1.1901
|View full text |Cite
|
Sign up to set email alerts
|

Beneficios del aprendizaje cooperativo en las áreas troncales de Primaria: Una revisión de la literatura científica

Abstract: El aprendizaje cooperativo se viene utilizando en educación primaria como alternativa a métodos educativos tradicionales y competitivos. El objetivo de este estudio es mostrar los beneficios académicos, afectivos y sociales del aprendizaje cooperativo en las áreas troncales de la educación primaria (lengua castellana, matemáticas, ciencias naturales, ciencias sociales e inglés). Para localizar los trabajos se accede a las bases de datos: Dialnet, ERIC, ScienDirect y Scielo. Finalmente, se analizan un total de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Se logra establecer un entorno propicio para el aprendizaje, en el cual los niños experimentan seguridad, inclusión, aceptación y motivación para participar activamente en las actividades escolares, de este modo llega a alcanzar el éxito académico. La adquisición de habilidades sociales ayuda a resolver conflictos de manera pacífica, lo cual contribuye a crear un ambiente escolar armonioso que fomenta un desarrollo positivo dentro del aprendizaje ( Boix & Ortega, 2020).…”
Section: Desarrollo De Habilidades Sociales En La Infancia Y Su Influ...unclassified
“…Se logra establecer un entorno propicio para el aprendizaje, en el cual los niños experimentan seguridad, inclusión, aceptación y motivación para participar activamente en las actividades escolares, de este modo llega a alcanzar el éxito académico. La adquisición de habilidades sociales ayuda a resolver conflictos de manera pacífica, lo cual contribuye a crear un ambiente escolar armonioso que fomenta un desarrollo positivo dentro del aprendizaje ( Boix & Ortega, 2020).…”
Section: Desarrollo De Habilidades Sociales En La Infancia Y Su Influ...unclassified
“…This indicates that research is more focused on the mathematical, social, communicative, and natural development in primary level classrooms. This is because they are the core areas, that are the main areas that allow for the development and impact with everyday surroundings (Vilella & Rodríguez, 2020). It was also observed that the application of serious games was not focused on the development of any single area, but rather on the contrary; since they could be adapted for the development of all areas, making them thereby an even more useful and versatile tool in the classroom.…”
Section: Developed Application Areas Of Serious Gaming 431 the Areas ...mentioning
confidence: 99%
“…In the face of the current circumstances, generated by the pandemic and technology, students spend more time in the activities related to games (Homer et al, 2012), which represent an opportunity to adapt these environments as an alternative method (Ronimus et al, 2019) that responds to learning objectives. However, these premises lead to a rethinking of the educational scenario;, since games require time to learn the use of technological materials, pedagogical and technical support, and digital access, as well as gap capacity, which needs to be examined (Hanna et al, 2021;Rodríguez, 2020). And this makes it difficult to choose the most suitable serious game (Muñoz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%